Mandatory retirement rules and the retirement decisions of university professors in Canada - Casey Warman; Christopher Worswick (Queen's University, Department of Economics, 2009)
We examine the impact of mandatory retirement on the retirement decisions of professors in Canada using administrative data. We find that the age distributions of professors at universities without mandatory retirement and those at universities with mandatory retirement at age 65 have diverged over time with a higher fraction of professors over the age of 65 being at universities without mandatory retirement. Estimation of a discrete time hazard model indicates that faculty members at universities with mandatory retirement at age 65 have exit rates at age 65 that are around 30 to 36 percentage points higher than those of their counterparts at universities without mandatory retirement. Similar results are found for both men and women; however, the magnitude of this effect is somewhat smaller for women.
Keywords: I23; J14; J18; J21; J26; J45; 330; University; Faculty; Retirement; Rentenpolitik; Altersgrenze; Gesetzliche Rentenversicherung; Hochschullehrer; Kanada